2017
DOI: 10.1016/j.pmrj.2017.08.436
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dimorphism in Central Adiposity May Explain Metabolic Dysfunction After Spinal Cord Injury

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…These changes in body fat distribution occur in conjunction with excessive production of hepatic glucose in the absence of autonomic nervous system control after SCI in those with injuries above the fourth thoracic segment [59]. The increase in VAT is negatively related to high density lipoprotein cholesterol (HDL-C) and insulin resistance, with men being 1.8-2.6 times more susceptible to accumulation of VAT than women after SCI [60]. Several anthropometric and imaging measurements have been proposed to accurately quantify changes in muscle size and visceral adiposity [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…These changes in body fat distribution occur in conjunction with excessive production of hepatic glucose in the absence of autonomic nervous system control after SCI in those with injuries above the fourth thoracic segment [59]. The increase in VAT is negatively related to high density lipoprotein cholesterol (HDL-C) and insulin resistance, with men being 1.8-2.6 times more susceptible to accumulation of VAT than women after SCI [60]. Several anthropometric and imaging measurements have been proposed to accurately quantify changes in muscle size and visceral adiposity [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies clearly demonstrated that increase in VAT CSA [31,32] is tightly associated with cardiometabolic disorders after SCI, especially when VAT CSA exceeded 100 cm 2 . MRI and CT are considered the gold standard techniques in quantifying VAT; however, the existing hurdles (ie, cost, accessibility, and duration of the analysis and ionized radiation in CT) are prohibitive and preclude their use in clinical settings or in large epidemiologic studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…MRI and CT are considered the gold standard techniques in quantifying VAT; however, the existing hurdles (ie, cost, accessibility, and duration of the analysis and ionized radiation in CT) are prohibitive and preclude their use in clinical settings or in large epidemiologic studies [15]. Advances in imaging technology have helped establishing the independent associations of VAT to cardiometabolic risk factors [30‐34], which is independent of other changes in body composition [5,17]. However, findings were primarily challenged by the small sample size, and therefore establishing a VAT prediction equation may allow enrollment of large sample sizes to decipher the exact mechanism by which VAT may influence an individual's cardiometabolic profile after SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations